Progress in the efficacy and mechanism of spinal cord stimulation in neuropathological pain. Issue 1 (2nd March 2022) - Li, Shun‐Lian; Li, Jing; Xu, Hui‐Chan; Liu, Yu‐Cong; Yang, Ting‐Ting; Yuan, Hao
Abstract: Neuropathic pain (NP) is a long‐term recurrent disease caused by somatosensory nervous system injury, with spontaneous pain, hyperalgesia, ectopic pain, and paresthesia as the main clinical manifestations. It adversely affects patients' quality of life. NP treatments often include medication, physical therapy, and invasive therapy; the first two therapies are generally ineffective for some NP patients. These patients sometimes rely on invasive therapy to alleviate pain. Spinal cord stimulation (SCS) is a very effective therapeutic method. SCS is a neuroregulatory method that involves placing the electrodes on the corresponding painful spinal cords. Pain is greatly alleviated after SCS. SCS has been proven to be an effective therapeutic method for the treatment of neurological pain. Furthermore, SCS provides a feasible approach for patients with unsuccessful drug treatment. This paper reviews the relevant literature of spinal cord electrical stimulation, focusing on the mechanism of action, clinical application, clinical efficacy and technical progress of spinal cord electrical stimulation. SCS is widely used in the treatment of NP diseases such as postherpetic neuralgia, back surgery failure syndrome, and phantom limb pain. With advancements in science and technology, tremendous progress has also been made in the spinal cord electrical stimulation method and good momentum has been maintained. Abstract : The components of the image are redirected to tell the story from top to bottom. For the sake of simplicity, I have used the two most representative diagrams to illustrate my review. The review focuses on the latest mechanisms and applications of SCS.